When practice does not make a perfect - paradoxical learning curve in schizophrenia and bipolar disorder revealed by different serial reaction time task variants - Chrobak, Adrian Andrzej; Siuda-Krzywicka, Katarzyna; Soltys, Zbigniew; Bielak, Sylwia; Nowaczek, Dominik; Żyrkowska, Aleksandra; Fafrowicz, Magdalena; Marek, Tadeusz; Pęcherzewska, Ewa; Kużdżał, Jan; Starowicz-Filip, Anna; Gorostowicz, Aleksandra; et al. (Frontiers in Psychiatry, 2023)
Our previous studies identified paradoxical implicit motor learning curve in schizophrenia (SZ) and bipolar disorder (BD) patients. The aim of this study was to verify whether those previously observed deficits may be captured by a new version of the ambidextrous Serial Reaction Time Task (SRTT), prepared for the use in the MRI.This study involved 186 participants. 97 participants (33 BD, 33 SZ and 31 healthy controls, HC) completed original, unlimited time response variant of SRTT. 90 individuals (30 BD, 30 SZ, 30 HC) underwent newer, limited response time version of this procedure. There was no significant difference in terms of implicit motor learning indices between both limited and unlimited response time SRTT. Compared to HC, SZ and BD patients presented decreased indices of implicit motor learning. Both clinical groups showed a paradoxical learning pattern which differed significantly from the HC. Moreover, in the SZ group, the pattern depended on the hand performing SRTT. Limited response time SRTT variant allowed us to replicate the findings of disrupted implicit motor learning in SZ and BD. The use of this paradigm in further neuroimaging studies may help to determine neuronal underpinnings of this cognitive dysfunction in abovementioned clinical groups.